Motivasi Kerja Dengan Job Insecurity Pada Karyawan Kontrak - Paramita, Niken; Mulyani, Mulyani; Komalasari, Shanty (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2022)
AbstractThe purpose of this study was to determine the relationship between work motivation and job insecurity in contract employees in private companies. The method used in this research is the descriptive quantitative research method. The subjects in this study were employees with contract status in the company with 15 contract employees. Sampling using saturated sampling technique because the population is used as a whole as the research sample. The data used is quantitative data with data collection using a questionnaire method in the form of a scale and interviews. The research quantitative data were analyzed using a descriptive statistics test with a mean value of 46.93 and a standard deviation of 5.812 for work motivation and a mean value of 38.13 and a standard deviation of 4.406 for job insecurity. The results of the correlation calculation using the Spearman rank correlation coefficient test are known to be the Sig. (2-tailed) of 0.356. Meanwhile, the correlation coefficient value is 0.257 so it can be interpreted that the level of strength of the correlation coefficient relationship between work motivation variables and job insecurity is at a very low level. The percentage of effective contribution of work motivation affecting job insecurity based on the results of the determination test is only 0.054 or 5.4% and the remaining 94.6% is influenced by other factors not included in this study.